The anti-intellectual presidency the decline of presidential rhetoric from George Washington to George W. Bush - Lim, Elvin T. 1976- (Oxford University Press, 2008)
Elvin Lim draws on interviews with more than 40 presidential speechwriters to investigate this relentless qualitative decline, over the course of 200 years, in our presidents' ability to communicate with the public.